Maternal profiles and social determinants of severe acute malnutrition among children under-five years of age: A case-control study in Nepal - Ahmed Hossain; Bhupendra Niroula; Sangita Duwal; Shakil Ahmed; Md. Golam Kibria (Heliyon, 2020)
Background: Addressing the determinants of severe acute malnutrition (SAM) among children remains a challenge in Nepal. This study investigated the effect of maternal and social determinants of SAM among under-five children of Nepal. Methods: We conducted a hospital-based unmatched case-control study with 256 under-five children (128 cases and 128 controls). The children aged 6–59 months were taken, and the cases and controls were defined based on mid-upper arm circumference (MUAC). Results: Backward Stepwise logistic regression analysis of 6–59 months children showed that the odds of SAM were lower among male children (AOR = 0.50, 95% CI = 0.27–0.92), mothers from high socioeconomic status (AOR = 0.469, 95% CI = 0.26–0.83), breastfeeding 6–12 months (AOR = 0.21, 95% CI = 0.05–0.68), breastfeeding ≥13 months (AOR = 0.18, 95% CI = 0.05–0.54) and optimal complementary feeding (AOR = 0.40, 95% CI = 0.22–0.70). SAM was significantly higher among children of the age group 6–24 months (AOR = 2.57, 95% CI = 1.30–5.22) and children with a history of diarrhea (AOR = 1.75, 95% CI = 0.92–3.39). Conclusions: In order to reduce the children's SAM, it is necessary to scale up services to improve the socioeconomic status which includes the education, occupation, and monthly income of the mother. Girls of age group 6–24 months were more likely to develop SAM. Two contributing factors to decrease SAM are the importance of exclusive breastfeeding practices and the availability and usage of soap in hand washing, which are ideal for low cost interventions. To reduce SAM in Nepal, a focus on enhancing complementary feeding through increased affordability of nutritious foods is also needed.